NLRP3 inflammasome as a therapeutic target in doxorubicin-induced cardiotoxicity: role of phytochemicals - Zhao, Xiao-Peng; Duan, Lian; Zhao, Qian-Ru; Lv, Xing; Tian, Nai-Yuan; Yang, Sheng-Lei; Dong, Kun (Frontiers in Pharmacology, 2025)
Doxorubicin (DOX) has received widespread attention as a broad-spectrum antitumor drug. However, it has been a recognized challenge that long-term DOX injections can lead to severe cardiotoxicity. There are numerous interventions to DOX-induced cardiotoxicity, and the most cost-effective is phytochemicals. It has been reported that phytochemicals have complex and diverse biological properties, facilitating the mitigation of DOX-induced cardiotoxicity. DOX-induced cardiotoxicity has numerous pathological mechanisms, and the nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome-mediated cardiomyocyte pyroptosis is one of them. This review initially presents an overview of the pathological mechanisms that underlie cardiotoxicity induced by DOX. Subsequently, we present a comprehensive elucidation of the structure and activation of the NLRP3 inflammasome. Finally, we provide a detailed summary of phytochemicals that can mitigate DOX-induced cardiotoxicity by influencing the expression of the NLRP3 inflammasome in cardiomyocytes.